2016
DOI: 10.1371/journal.pone.0164209
|View full text |Cite
|
Sign up to set email alerts
|

Root Parameters Show How Management Alters Resource Distribution and Soil Quality in Conventional and Low-Input Cropping Systems in Central Iowa

Abstract: Plant-soil relations may explain why low-external input (LEI) diversified cropping systems are more efficient than their conventional counterparts. This work sought to identify links between management practices, soil quality changes, and root responses in a long-term cropping systems experiment in Iowa where grain yields of 3-year and 4-year LEI rotations have matched or exceeded yield achieved by a 2-year maize (Zea mays L.) and soybean (Glycine max L.) rotation. The 2-year system was conventionally managed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 64 publications
3
27
0
Order By: Relevance
“…The vast majority of SOC (> 90 %) was associated with silt and clay particles at all soil depths, a finding that is consistent with results from other fractionation studies conducted on finely-textured Mollisols of the Midwest U.S. (Brown et al, 2014;Cates and Ruark, 2017;Lazicki et al, 2016). However, the distribution of MAOM between the microaggregate-associated silt plus clay (μSilt + Clay) and easily-dispersed silt plus clay (dSilt + Clay) shifted with depth, probably reflecting decreasing amounts of plant-and microbial-derived C and associated biological activity.…”
Section: Vertical Patternssupporting
confidence: 89%
“…The vast majority of SOC (> 90 %) was associated with silt and clay particles at all soil depths, a finding that is consistent with results from other fractionation studies conducted on finely-textured Mollisols of the Midwest U.S. (Brown et al, 2014;Cates and Ruark, 2017;Lazicki et al, 2016). However, the distribution of MAOM between the microaggregate-associated silt plus clay (μSilt + Clay) and easily-dispersed silt plus clay (dSilt + Clay) shifted with depth, probably reflecting decreasing amounts of plant-and microbial-derived C and associated biological activity.…”
Section: Vertical Patternssupporting
confidence: 89%
“…The lack of a significant cropping system effect on gross ammonification in the present study is likely due in part to limited cropping system effects on SOM. While the diversified cropping systems did maintain modestly greater labile soil C (particulate organic matter C) compared to the 2-year system in the top 20 cm of soil (Lazicki et al 2016), similar differences could not be observed in the total SOM pool despite 12 years of consistent management differences between the cropping systems (Appendix), possibly because our experiment was established on Mollisols with high pre-existing SOM levels that may be C saturated (Brown et al 2014). Thus the modest differences in labile C may not have led to observable changes in gross ammonification.…”
Section: Discussionmentioning
confidence: 93%
“…Alternatively, improved soil physical properties (e.g., lower bulk density; Table 1) may have allowed roots to access water and nutrients more easily in plots with greater SOC content, increasing yield potential and NR crop (Unger and Kaspar, 1994). In another Iowa study, Lazicki et al (2016) reported higher yields and greater root length density of maize grown in cropping systems receiving more organic C inputs. Further research on root growth characteristics and root fertilizer N recovery across gradients of SOM may help to explain the curvilinear response NR crop observed in our study.…”
Section: Legacy Effects Of N Fertilizer Rate On Crop and Soil Fertilimentioning
confidence: 99%